Green light powered molecular state motor enabling eight-shaped unidirectional rotation - Aaron Gerwien (Nature Portfolio, 2019)
Molecular motors have predominantly been limited to circular or linear directional motions. Here, the authors design a molecular motor that moves unidirectionally along a more complex figure-eight trajectory by a distinct four-step mechanism that alternates between photochemical and thermal reaction steps.